2006
DOI: 10.1093/ndt/gfl069
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect economic costs incurred by living kidney donors—a systematic review

Abstract: Donors incur many types of costs attributable to kidney donation and the total costs are certainly higher than previously reported. To guide informed consent and fair reimbursement policies, further data on all relevant costs, preferably from a detailed prospective multi-centre cohort study, are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
104
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 50 publications
5
104
0
2
Order By: Relevance
“…In our study, some respondents were denied health or life insurance (1.8% and 2.1%, respectively). Given the demographic characteristics of respondents versus nonrespondents, we believe those are an underestimate: More nonrespondents were from groups (younger, male, and ethnic minorities) that are less likely to have health insurance at donation (42). Additionally, lack of health insurance may impede some from seeking medical or psychological follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, some respondents were denied health or life insurance (1.8% and 2.1%, respectively). Given the demographic characteristics of respondents versus nonrespondents, we believe those are an underestimate: More nonrespondents were from groups (younger, male, and ethnic minorities) that are less likely to have health insurance at donation (42). Additionally, lack of health insurance may impede some from seeking medical or psychological follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These may include direct out-of-pocket expenses (i.e., travel, lodging, meals, parking, dependent care, and some uncovered medical expenses) and indirect costs (i.e., lost wages, use of employer-sponsored paid time off, and effect of insurability or premium rates) (Table 1) (4). Total estimated costs for LKDs range from $0-$20,000, with an average of approximately $5000 (4,16,17). In a 2014 Canadian study, Klarenbach et al reported that 96% of LKDs had experienced negative financial consequences from donation, with 47% reporting lost wages (16).…”
Section: Background On Systemic Barriers To Living Kidney Donationmentioning
confidence: 99%
“…The LDKT and LKD financial concerns of patients and potential donors are not unfounded (41)(42)(43). The workgroup noted the likelihood that the financial effect of LKD is a significant driver of disparities in LDKT, both for those in lower socioeconomic classes and for many members of minority groups.…”
Section: Incomementioning
confidence: 99%
“…Although this topic was explored in more depth in another workgroup (44), the finances of access to care and burdens of LKD were central to our workgroup's discussion. Unfortunately, living donor costs have not been systematically captured by the transplant community, although some have estimated total costs to range from $0 to $20,000, with an average of approximately $5000 (41)(42)(43)45). Concern about these costs deters both transplant candidates from talking to others about possible donation and potential living donors from pursuing donation (46).…”
Section: Incomementioning
confidence: 99%